“Must everything give way to the automobile?”: The Ancaster and Dundas Expressway Disputes in Ontario, 1967-1968 - Robinson, Danielle (Ontario History)

(untitled) (The Ontario Historical Society, 2008)
In Ontario in the late 1960s, the provincial government’s plan to build an expressway through the Ancaster-Dundas region sparked widespread protests from local residents. Objectors who vehemently opposed the proposals before they were officially tabled protested only more vigorously as the controversy wore on, until the plans were ultimately shelved indefinitely. The conflict between government officials and residents over the ways in which postwar planning and development would affect the region offers valuable insights into the public and political mood of the late 1960s in southern Ontario. As government officials sought to support sprawling development and increased demand on transportation networks, citizens mobilized to defend not only the rapidly dwindling natural environment, but also their own communities. The case of the expressway proposals involves emblematic themes dominating Canadian post World War II urban and suburban history, exemplified by one protestor’s simple and direct plea – “Must everything give way to the automobile?”